Ocena wybranych platform do e-Learningu pod względem dostępności dla osób z niepełnosprawnościami i zgodności z zasadami projektowania uniwersalnego - Królak, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Popularity of using learning management systems (LMS) is increasing all over the world. The main function of such tools is to facilitate teaching and learning and enable distance education. It is therefore very important to adjust the e-learning platforms to the needs of students and teachers with disabilities. In this paper the rules of universal design for ICT are presented and World Wide Web Consortium (W3C) recommendations for designing web content are discussed. Five e-learning platforms were tested if they fulfill the requirements of above mentioned regulations: WIKAMP, Moodle, Sakai, Fronter and ItsLearning. The results of this analysis are presented and discussed
Keywords: Learning Management System; e-learning; universal design for ICT, ATAG; educationof the disabled